Anti‐tumour effects of a dual cancer‐specific oncolytic adenovirus on Breast Cancer Stem cells. Issue 2 (11th December 2020) - Li, Wenjie; Li, Yiquan; Cui, Yingli; Li, Shanzhi; Zhu, Yilong; Shang, Chao; Song, Gaojie; Liu, Zirui; Xiu, Zhiru; Cong, Jianan; Li, Tingyu; Li, Xiao; et al.
Abstract: Apoptin can specifically kill cancer cells but has no toxicity to normal cells. Human telomerase reverse transcriptase (hTERT) can act as a tumour‐specific promoter by triggering the expression of certain genes in tumour cells. This study aims to investigate the inhibitory effects and to explore the inhibitory pathway of a dual cancer‐specific recombinant adenovirus (Ad‐apoptin‐hTERTp‐E1a, Ad‐VT) on breast cancer stem cells. Breast cancer cell spheres were obtained from MCF‐7 cells through serum‐free suspension culture. The cell spheres were detected by flow cytometry for CD44 + CD24 − cell subsets. The stemness of MCF‐7‐CSC cells was confirmed by in vivo tumorigenesis experiments. The inhibitory effect of the recombinant adenoviruses on MCF‐7‐CSC cells was evaluated by CCK‐8 assay. In addition, the stemness of adenovirus‐infected MCF‐7‐CSC cells was analysed by testing the presence of CD44 + CD24 − cell subsets. The ability of the recombinant adenovirus to induce MCF‐7‐CSC cell apoptosis was detected by staining JC‐1, TMRM and Annexin V. Our results showed that a significantly higher proportion of the CD44 + CD24 − cell subsets was present in MCF‐7‐CSC cells with a significantly increased expression of stem cell marker proteins. The MCF‐7‐CSC cells, whlist exhibited a strong tumorigenic ability with a certain degree of stemness in mice, were shown to be strongly inhibited by recombinant adenovirus Ad‐VT through cell apoptosis. In addition, Ad‐VT was shown to exert a killing effect on BCSCs. These results provide a new theoretical basis for the future treatment of breast cancer.